An unusual p53 mutation detected in Burkitt's lymphoma: 30 bp duplication - Šmardová, Jana; Nikulenkov Grochová, Diana; Fabian, Pavel; Moulis, Mojmír; Šmarda, Jan; Falková, Iva; Ravčuková, Barbora; Vaňková, Jana; Vášová, Ingrid (Oncology reports, 2008)
Burkitt's lymphomas (BL) are aggressive rapidly growing tumors typified by a high c-myc expression resulting from t(8;14)(q24;q32), t(2;8)(p12;q24) or t(8;22)(q24;q11) translocations. Alterations of the p53 tumor suppressor are also relatively frequent in BL. Several approaches have been adopted for detection of the p53 aberrations such as immunohistochemical analyses, immunoblotting, DNA sequencing, fluorescence in situ hybridization (FISH), and functional assays. We used these methods to characterize the p53 mutation in tumor cells of a 53-year-old male suffering from Burkitt's lymphoma. By immunohistochemical analyses, we detected high levels of the p53 protein in the tumor tissue. Immunoblotting showed a higher molecular weight of the p53 protein overexpressed in the tumor tissues than that of the standard p53 protein. Similarly, the molecular weight of the PCR product prepared by amplification of the tumor p53 cDNA was higher than that of the standard p53 cDNA. Functional analyses of separated alleles in yeast evidently revealed that the tumor p53 protein was transcriptionally non-functional. The yeast colonies expressing this p53 variant possessed a unique phenotype in that they were red with many white spots on their surface. Sequencing of the tumor cDNA revealed a duplication of the 30 bp region of the p53 gene (g.12155_12184dup30) leading to a repeat of 10 amino acids (Pro-77 to Ala-86) in the p53 protein. Further analyses showed that the mutation was unstable in yeast cells. The FISH analyses did not confer loss of the p53-specific locus 17p13.
Keywords: duplikace genu; Gene Duplication; Reverse Transcriptase Polymerase Chain Reaction; Humans; hybridizace in situ fluorescenční; Mutation; lidé středního věku; Middle Aged; In Situ Hybridization, Fluorescence; Financing, Organized; geny p53; financování organizované; DNA, Complementary; mužské pohlaví; Tumor Suppressor Protein p53; Genes, p53; komplementární DNA; polymerázová řetězová reakce s reverzní transkripcí; nádorový supresorový protein p53; Burkittův lymfom; Burkitt Lymphoma; lidé; mutace; Male